Variation in term birthweight across European countries affects the prevalence of small for gestational age among very preterm infants. (8th June 2017) - Zeitlin, Jennifer; Bonamy, Anna‐Karin Edstedt; Piedvache, Aurelie; Cuttini, Marina; Barros, Henrique; Van Reempts, Patrick; Mazela, Jan; Jarreau, Pierre‐Henri; Gortner, Ludwig; Draper, Elizabeth S.; Maier, Rolf F.; ,
Abstract: Aim: This study assessed the prevalence of small for gestational age (SGA) among very preterm (VPT) infants using national and European intrauterine references. Methods: We generated country‐specific and common European intrauterine growth references for 11 European countries, according to Gardosi's approach and Hadlock's foetal growth model, using national data on birthweights by sex. These references were applied to the Effective Perinatal Intensive Care in Europe (EPICE) cohort, which comprised 7766 live VPT births without severe congenital anomalies under 32 weeks of gestation in 2011–2012, to estimate the prevalence of infants with SGA birthweights, namely those below the 10th percentile. Results: The SGA prevalence was 31.8% with country‐specific references and 34.0% with common European references. The European references yielded a 10‐point difference in the SGA prevalence between countries with lower term birthweights (39.9%) – Portugal, Italy and France – and higher term birthweights, namely Denmark, the Netherlands, Sweden (28.9%; p < 0.001). This was not observed with country‐specific references, where the respective figures were 32.4% and 33.9% (p = 0.34), respectively. Conclusion: One‐third of VPT infants were SGA according to intrauterine references. Common European references showed significant differences in SGA prevalence between countries with high and low‐term birthweights.